Synthetic Osmotic Dilator Prior to Induction of Labor: Outcomes From International Observational E-Registry [13C]. (May 2017) - Saad, Antonio; Gupta, Janesh; Maier, Josefine; Hruban, Lukas; Mehta, Priyanka; Baev, Oleg
Abstract : INTRODUCTION: To determine rate of cesarean delivery (CD) and maternal/neonatal adverse outcomes associated with use of synthetic osmotic dilator prior to labor induction. METHODS: This is a multicenter international post-marketing observational study of a synthetic osmotic dilator (Dilapan-S) for cervical ripening prior to labor induction in term pregnancies. Our primary outcome was rate of CD. Data were obtained in a standardized fashion and entered into a centralized electronic data capture system for analysis. RESULTS: Between May 2015 and July 2016, 343 term pregnant women undergoing cervical ripening prior to labor induction were included. Median maternal age was 30 (IQR18-45) years, and average BMI was 27. 68% of participants were nulliparous, 23% had a previous vaginal delivery and 9% had previous cesarean section. The majority (64%) of women received 4-5 dilators and the CD rate was 32%. Bishop score gain was 3.7 (95% CI [3.4-3.9]) with the use of the dilator. There were no cases of uterine tachysystole or FHR abnormalities. Maternal discomfort was reported by 9% of women and the rate of chorioamnionitis was 1.5%. Meconium stained amniotic fluid was present in 11% of patients. All newborns had an Apgar score at 5 minutes ≥ 7. Arterial pH < 7.1 and neonatal intensive care admissions were < 1%. CONCLUSION: Compared to other cervical ripening methods, the use of synthetic osmotic dilators appears to be safe and efficient method of cervical ripening for induction of labor in term pregnant women. Randomized clinical trials are needed to compare its efficacy to other methods of cervical ripening.